Management Aspects of Land Leasing: Foreign and Domestic Experience - Gryshko, Volodymyr; Khrystenko, Olena; Gubar, Olena; Maksymenko, Oksana (International Journal of Engineering and Technology, 2018)
The article describes domestic and foreign experience in land management practices, in particular, aspects of land lease. The authors conducted a study of the effectiveness of land management, depending on the terms of land lease, as well as possible conflicts among the main stakeholders. It is determined that the main factors for ensuring the effectiveness of land management are as follows: an effective management and an institutional regulation of integrated activities aimed at the realization of environmental and economic interests. The method of dynamic programming and game theory method was applied, which made it possible to determine the respective strategic positions of the landlord and tenant.Â Â